Advancing women’s nutrition by leveraging women’s groups and movements in South Asia: Potential opportunities - Shrivastav, Monica; Desai, Sapna; Hazra, Avishek (Population Council Institute, India, 2023)
Adolescent girls and women face multiple barriers to consume diverse and nutrient-rich diets, access to resources, and care for nutrition. Women’s groups and movements have emerged as strong social, financial, and health forces with potential to address complex challenges in South Asia. Women’s groups have a long history in the region, advancing women’s representation in political space, improving education, reducing violence and addressing poverty. Extensive experimentations have been done through communitybased women’s groups to improve nutritional outcomes of women and children. To identify interventions, elicit pathways, and synthesize approaches of women’s groups that address social determinants impacting nutrition, we did a scoping review and mapping study across six South Asian countries. Women’s groups address diverse domains including microfinance, livelihoods, women’s health, and nutrition and violence against women. They act at three levels—grassroots mobilization, programmatic actions, and policy advocacy toward creating an enabling environment and access to food and services. We identified two priorities—investment in integrated food-systemsrights pathways and building coalitions of women’s organizations and movements. The basic tenets of group/movement-based engagement, i.e., womencentered and women-led programming, strengthening social capital and leadership while building networks and community advocacy, are instructive in how to improve future nutrition programming in South Asia. Working with women’s groups and movements can ensure justice and equity in nutrition agendas, where women are at the forefront of deciding their priorities, demanding their rights and services, and through collective action, acting and pushing for social change and accountability.